An Application of Contextualised Knowledge Elicitation in the Development of Knowledge Management Systems based on Identified Critical Success Factors - Sukumaran, Sanath (2018)
A significant number of ineffective Knowledge Management Systems inundating the marketplace today necessitates the identification of critical success factors prior to the development of successful Knowledge Management Systems. Critical Success Factors (CSF) that embody contextual elements are investigated and determined to form a contextual-based framework that would be useful for KMS developer in building a KMS while taking into consideration of elements beyond merely technical dimensions. The framework guides the knowledge elicitation process to acquire contextual aspects from knowledge workers among others. In building the framework, a mixed mode data gathering method was adopted to investigate KM practices and KMS implementations across five organisations from various industries. A purposive sampling was used for the survey followed by semi-structured interviews. The findings led to a refined list of six (6) Critical Success Factors governing contextual knowledge elicitation namely KM Strategy, Knowledge Repository, KM Measurement Metrics, Core KM Features, Motivational Factors and KM Governance. In order to formulate the theoretical framework, activity theory and knowledge value added were used as the theoretical underpinning. The outcome of the theoretical contributions are the KMS-AT Development Framework, the Knowledge Asset Value Stream Model, the KM-AT Model and the KM Measurement Metrics. The practical contributions of this research include the KMS Business Case Blueprint and the KMS Requirements Blueprint. The culmination of the research is the validation of the KMS-AT Development Framework through the development and deployment of a prototype knowledge elicitation tool for acquiring contextual knowledge in building Knowledge Management Systems.